Quantifying N2 fixation and its contribution to export production near the Tonga-Kermadec Arc using nitrogen isotope budgets - Forrer, Heather J.; Bonnet, Sophie; Thomas, Rachel K.; Grosso, Olivier; Guieu, Cecile; Knapp, Angela N. (Frontiers in Marine Science, 2023)
The spatial distribution of marine di-nitrogen (N2) fixation informs our understanding of the sensitivities of this process as well as the potential for this new nitrogen (N) source to drive export production, influencing the global carbon (C) cycle and climate. Using geochemically-derived δ15N budgets, we quantified rates of N2 fixation and its importance for supporting export production at stations sampled near the southwest Pacific Tonga-Kermadec Arc. Recent observations indicate that shallow (<300 m) hydrothermal vents located along the arc provide significant dissolved iron to the euphotic zone, stimulating N2 fixation. Here we compare measurements of water column δ15NNO3+NO2 with sinking particulate δ15N collected by short-term sediment traps deployed at 170 m and 270 m at stations in close proximity to subsurface hydrothermal activity, and the δ15N of N2 fixation. Results from the δ15N budgets yield high geochemically-based N2 fixation rates (282 to 638 µmol N m-2 d-1) at stations impacted by hydrothermal activity, supporting 64 to 92% of export production in late spring. These results are consistent with contemporaneous 15N2 uptake rate estimates and molecular work describing high Trichodesmium spp. and other diazotroph abundances associated with elevated N2 fixation rates. Further, the δ15N of sinking particulate N collected at 1000 m over an annual cycle revealed sinking fluxes peaked in the summer and coincided with the lowest δ15N, while lower winter sinking fluxes had the highest δ15N, indicating isotopically distinct N sources supporting export seasonally, and aligning with observations from most other δ15N budgets in oligotrophic regions. Consequently, the significant regional N2 fixation input to the late spring/summer Western Tropical South Pacific results in the accumulation of low-δ15NNO3+NO2 in the upper thermocline that works to lower the elevated δ15NNO3+NO2 generated in the oxygen deficient zones in the Eastern Tropical South Pacific.